Pemetaan Sebaran Rajungan yang ditangkap menggunakan Bubu Di Perairan Pesisir Barat Lampung - Aprilia Syah Putri; Mulkan Nulzapril; Denta Tirtana (Universitas Pattimura, 2023)
The Pesisir Barat of Lampung is one of the locations that has great opportunities for capture fisheries activities in Lampung. The abundant potential of these waters means that people in Pesisir Barat Regency earn income from fishing along these waters. Fishermen still catch fish using traditional tools using small boats (jukung). The vast waters with muddy and sandy water substrates make fishermen use fishing gear that is cheap, easy to operate and environmentally friendly. The trap fishing gear is a passive fishing gear operated by fishermen whose main catch is crab. The aim of this research is to map the distribution of crab catches using trap fishing gear. This research was carried out from June 2023 to September 2023. The research location was carried out in West Coastal Waters. Mapping crab fishing areas begins with identifying crab fishing areas. Identification of crab fishing areas is carried out using a survey method on three indicators, namely the location of fishing operations, catch results and environmental conditions. These results show that the distribution of crabs using trap fishing gear on the West Coast is at the Fishing Ground in Kuala Stabas Waters, Bengkunat Bay Waters and Labuhan Tapokan Waters with the number of crabs on LED trap fishing gear being 250 and the number of crabs on trap fishing gear without LEDs being 250. 119 Tails